Microfungi associated with ornamental palms: Byssosphaeria phoenicis sp. nov. (Melanommataceae) and Pseudocoleophoma rhapidis sp. nov. (Dictyosporiaceae) from south China - Kularathnage, Nuwan D.; Wanasinghe, Dhanushka N.; Senanayake, Indunil C.; Yang, Yunhui; Manawasinghe, Ishara S.; Phillips, Alan J.l.; Hyde, Kevin D.; Dong, Wei; Song, Jiage (Phytotaxa, 2022)
The health and attractiveness of ornamental plants play key role in gardening and horticulture. They affect both the economical and ornamental value of the plants. In this study, we collected and isolated microfungi associated with dead petioles of dwarf date palm and living leaves of lady palm from Zhongkai University Garden, Guangzhou, China. Phylogenetic relationships were investigated based on multi-locus phylogeny of ITS, LSU, SSU and tef-1α sequence data. The morphology of the new collections was compared with all the relevant species. Based on the morphological comparison and multi-locus phylogeny, we introduce Byssosphaeria phoenicis sp. nov. and Pseudocoleophoma rhapidis sp. nov. in Melanommataceae and Dictyosporiaceae, respectively. Detailed descriptions and illustrations are provided with notes discussing allied species in Byssosphaeria and Pseudocoleophoma. Pathogenicity testing of P. rhapidis causing leaf spots on lady palm was proven and Koch’s postulates fulfilled. This is the first phytopathogenic Pseudocoleophoma species. The pathogenicity does not cause dieback, but the leaf spots reduce the aesthetical value of the plants.